Distribution Pattern of Giant Clams (Tridacnidae) in Tebabinga Reef, Derawan Island Waters, East Kalimantan: - Nugroho, Bimo Aji; Fauzi, Ahmad; Suciyati, Alfi (Masyarakat Moluska Indonesia, 2025)
Derawan Islands, East Kalimantan, experienced a decline in the population of clams (Tridacnidae) due to over-exploitation and environmental changes. Although there are seven species of clams in Indonesia, data on their distribution patterns and factors affecting their survival in this area are still limited. This study aims to analyze the distribution patterns of clams on Tebabinga Reef and the abiotic factors affecting their habitat. The method used was observation with sampling using the belt transect technique at seven observation stations. Data collected included the number of individuals, size, and environmental parameters such as temperature, salinity, and pH. In the study, three types of clams were found: T. crocea, T. kerasa, and T. squamosa. T. crocea had a clustered distribution pattern (Id = 1.01), while T. kerasa (0.84) and T. squamosa (0.79) had a uniform pattern. Based on the type of substrate in Tebabinga Reef, the species T. kerasa is most common on coral massive, rubble, and sand substrates. Habitat conditions in Tebabinga Reef support the life of clams, although some abiotic parameters such as salinity and DO are below the quality standards. In conclusion, this study provides an overview of the distribution pattern of clams and environmental factors that affect their survival, and it emphasizes the importance of sustainable management to protect this species from further exploitation.